Perbedaan kemampuan Komunikasi Matematika Siswa dengan Menggunakan Strategi Pembelajaran Ekspositori dan Inkuiri Pada teorema Phytagoras di MTs. Muallimin Aek Raso Tahun Pelajaran 2019/2020. - Eva Julyanti; Ari Asnah Hastuti Siregar (Jurnal Riset Pembelajaran Matematika, 2020)
This study aims to determine whether there are differences in students' mathematical communication skills using Expository and Inquiry Learning Strategies in Pythagorean theorem in MTs. Muallimin Aek Raso for the 2019/2020 academic year. The population in this study were all students of class VIII MTs Muallimin Aek Raso which consisted of 2 classes, namely class VIII1 and VIII 2. The sample in this research was using cluster random sampling, taken 2 classes, namely class VIII1 with a total of 20 students using a strategy. Expository learning and for class VIII2 consisted of 20 students using inquiry learning strategies. The instrument in this study consisted of a description test of 10 questions which were first tried out in another class whose aim was to see the quality of the test in the form of validity, reliability and difficulty level of the questions. From the data analysis, an average count of 84.15 was obtained with a standard deviation of 7.7 in class VIII1 while the average count was 75.45 with a standard deviation of 6.5 in class VIII2. From the Hypothesis Test Using the Anova Test at Level 5 % obtained tcount ¬ 1.75 and t table ¬ 0.444 Ho is rejected and Ha dite rima. Thus, the conclusion is that there are differences in students' mathematical communication skills using Expository and Inquiry Learning Strategies in the Pythagorean theorem in MTs. Muallimin Aek Raso for the 2019/2020 academic year.